2018
DOI: 10.1097/ccm.0000000000003068
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Laryngeal Air Column Width Difference as a New Predictor for Postextubation Stridor in Children

Abstract: Laryngeal air column width difference measurement may serve as a simple reliable noninvasive method for predicting postextubation stridor in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…The cuff leak test, or airway permeability test, with a high degree of diagnostic accuracy in the adult population 13 , does not have the same predictive capacity in the pediatric population 14 , especially in children under 7 years old 15 . Other less common methods, such as laryngeal ultrasound 16 and inductive inductance plethysmography 17 , even though they have shown good results in the identification of laryngeal edema, are still limited in clinical practice, since specific equipment and training are required for its management.…”
Section: Discussionmentioning
confidence: 99%
“…The cuff leak test, or airway permeability test, with a high degree of diagnostic accuracy in the adult population 13 , does not have the same predictive capacity in the pediatric population 14 , especially in children under 7 years old 15 . Other less common methods, such as laryngeal ultrasound 16 and inductive inductance plethysmography 17 , even though they have shown good results in the identification of laryngeal edema, are still limited in clinical practice, since specific equipment and training are required for its management.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these known risk factors, there is no clear system for delineating which patients may benefit from corticosteroid pretreatment prior to extubation. 5 The air leak test is often employed in an effort to determine which patients are at high risk for post-extubation stridor and extubation failure. There is significant variability in how this test is performed and what qualifies as a positive test.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with the air leak test in one pediatric study, ultrasound was found to be significantly more sensitive, specific, and accurate in predicting post-extubation stridor. 5 A Cochrane Systematic Review published in 2009 evaluated the effects of corticosteroids at reducing the risk for stridor and extubation failure in patients of all ages. 7 No difference in the rates of reintubation was observed when analyzing neonates and children separately.…”
Section: Introductionmentioning
confidence: 99%
“…Systemically, ultrasound technology has been applied to improve the accuracy of needle placement, particularly for difficult to identify or palpate regions or when great precision is required. Laryngeal anatomy is readily visualized on ultrasound and the technology is used in some protocols for diagnosing laryngeal pathology 7–11 . Ultrasound‐aided laryngeal intervention, however, is not widely reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal anatomy is readily visualized on ultrasound and the technology is used in some protocols for diagnosing laryngeal pathology. [7][8][9][10][11] Ultrasound-aided laryngeal intervention, however, is not widely reported in the literature. We describe a method of ultrasound-guided suture laterization which helps in accurate prediction of the needle trajectory minimizing repeated attempts while reducing the operative time.…”
Section: Introductionmentioning
confidence: 99%